Karakteristik Dakwah Salafiyah - Solahudin, Dindin (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung DJati Bandung, 2015)
Salafisme has long been developing into differentiation and divergence based on different interpretation and understanding on the practices of Salaf generation. Every stream of dakwah movement claims to follow salafi way of itâs own interpretation. This study aims at portraying one of salafi understanding and itâs salafi dakwah as a result. The resource of this study is Syaikh Muhammad al-GazÄlÄ« who is supposed to bear objective, original views and understanding on Salafism and salafi dakwah. The study shows that, since prophetic era, the first core character of of Salafism has been criticism so that salafi dakwah is not other than critical dakwah against wrong ways of dakwah and worse condition of the target umma. The second core has been constructivism, so that salafi dakwah has not been other than constructive dakwah that persue constructive efforts in building the umma consciousness. The last core has been moderation, so that salafi dakwah has not been other than moderate dakwah that promotes social equilibrium and justice.Â